The Impact of Education on the Innovation Performance in some EU Countries - Bene, Andrea; Csermák, József (Studia Mundi – Economica, 2024)
Innovation is not only of key importance for business strategy, it also determines the competitiveness of the national economy. The successful implementation of innovation processes requires knowledge and skills that must be provided by the nations’ educational institutions. Companies need a human resource that is prepared and has the right professional skills to face market challenges successfully in the long term. Current research also shows that the lack of IT skills, knowledge and experience needed to apply new technologies is a major obstacle to the innovation performance of organisations. This paper examines the indicators of the EU Innovation Scoreboard on the use of human resources and information technologies and highlights the key role of education.